"Being a team of five strong women... we had to make an impression:" The College Math Academy as an intervention into mathematics education. - Bhattacharya, Nandini; Langhout, Regina D.; Sylvane Vaccarino‐Ruiz, S.; Jackson, Natalya; Woolfe, Maya; Matta, Wendy; Zuniga, Britney; Rowe, Zella; Gibo, Leilani (American Journal of Community Psychology, 2022)
This paper, a first‐person account, describes a community psychology‐aligned intervention into a precalculus mathematics class at an Hispanic Serving Research Institution. The intervention was designed because the standard precalculus mathematics class had a high failure rate, especially for Latinx students, which was serving as a barrier for declaration of a Science, Technology, Engineering, or Mathematics major. The high failure rate indicates a structural problem that requires a structural intervention. The paper is coauthored with the teaching team, undergraduates who had taken the course, a graduate student who evaluated the class, and a community psychologist. We describe the ways that the new course, the College Math Academy, transformed the social environment through capacity building, providing access to valued resources for historically marginalized groups, facilitating opportunities to critique dominant power structures, prioritizing perspectives and experiences of people of color, and promoting understanding of how various social forces shape culture and values. The course also decentered white educational norms via adapting decoloniality and liberatory practices. In turn, each person describes their experience of the course. We draw on the first‐person accounts to show how they illustrate a transformative, decolonial, and liberatory social environment. We end with implications for how community psychologists can work in their universities to support structural change. Highlights: Changes to Precalculus class to better serve Latinx students.First person account of how structural course change shifted the classroom experience for students.Integration of a decolonial social enviornment intervention into a college math class.